Perspectives on the social and cultural impact of English as an international language - Jeffrey, David McLachlan (Philippine Journal of Linguistics, 2002)
The paper begins by examining the relationship between language, society and culture, which is used as a backdrop upon which to extend the debate by including the views of other theorists across the ideological divide concerning the social and cultural impact of English as an international language (ElL). Here, various aspects of ElL are discussed, such as its center-periphery dimensions, its propensity to marginalize other languages and cultures, the impact of globalization (including advances in communications technology) and the ownership of English by non-native speakers. The latter is considered an important turning point in the evolution of ElL, and examples of where this happened in Nigeria and the Philippines are used to illustrate this. Finally, the main conclusions reached in the paper are drawn together and highlighted, together with their implications for the English language teaching (ELT) profession.